Diagnostic Problem of Facial Malignancy in The Elderly: A rare case - Taurini, Dita; Ashariati, Ami; Bintoro, S. Ugroseno Yudho; Diansyah, M. Noor; Amrita, Putu Niken Ayu; Savitri, Merlyna; Romadhon, Pradana Zaky (Gaceta Médica de Caracas, 2023)
Introduction: Lymphoma can occur in adults and the elderly, this will affect the condition of both diagnosis and therapy. Plasmablastic lymphoma (PBL) is a subtype of diffuse large B-cell lymphoma (DLBCL), the case is rarely found and often overlaps the anatomical pathology picture similar to plasmacytoma. It is aggressive and often relapses.